2017
DOI: 10.15832/ankutbd.385863
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nuclear DNA Content and Ploidy of Hypericum perforatum L. Accessions Collected From Western Turkey

Abstract: Hypericum perforatum L. (St John's Wort) is a medicinal plant that produces pharmaceutically important compounds with antidepressive and anticancer activities. H. perforatum is a facultative apomictic species as it has the ability to reproduce with multiple reproduction mechanisms affecting genetic structure and chemical composition of the plants. The objective of this study was to determine nuclear DNA contents and ploidy levels of H. perforatum L. plants growing naturally in the flora of Turkey. The seeds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In some previous studies, a positive or negative correlation was reported between the altitude and genome size. For instance, researchers have described that in Indian maize populations (Rayburn and Auger, 1990), Vicia faba (Ceccarelli et al, 1995), Dasypyrum villosum (Caceres et al, 1998), tetraploid Festuca pallens (Smarda and Bures, 2006), O. pumila and A. montbretiana (Hoffmann et al, 2010), Pinus yunnanensis (Wang et al, 2013), Hypericum perforatum (Savaş Tuna et al, 2017), Allium populations (Guo et al, 2018), Zea mays (Bilinski et al, 2018), and Crepis (İnceer et al, 2018), there was a positive correlation between the altitude and genome size, similar to the results herein. On the other hand, other studies have reported a negative correlation between the altitude and genome size (Creber et al, 1994;Bottini et al, 2000;Chia et al, 2012;Manzaneda et al, 2012;Wang et al, 2013;Akbudak et al, 2018;Savaş Tuna et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some previous studies, a positive or negative correlation was reported between the altitude and genome size. For instance, researchers have described that in Indian maize populations (Rayburn and Auger, 1990), Vicia faba (Ceccarelli et al, 1995), Dasypyrum villosum (Caceres et al, 1998), tetraploid Festuca pallens (Smarda and Bures, 2006), O. pumila and A. montbretiana (Hoffmann et al, 2010), Pinus yunnanensis (Wang et al, 2013), Hypericum perforatum (Savaş Tuna et al, 2017), Allium populations (Guo et al, 2018), Zea mays (Bilinski et al, 2018), and Crepis (İnceer et al, 2018), there was a positive correlation between the altitude and genome size, similar to the results herein. On the other hand, other studies have reported a negative correlation between the altitude and genome size (Creber et al, 1994;Bottini et al, 2000;Chia et al, 2012;Manzaneda et al, 2012;Wang et al, 2013;Akbudak et al, 2018;Savaş Tuna et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Knight et al (2005) found that ecological and geographic changes had an effect. In addition, it has been shown that differences in climate (especially precipitation and temperature) and geography (location, region, altitude, and latitude) are associated with genome size variations and ploidy levels (Manzadena et al, 2012;López-Alvarez et al, 2015;Bareither et al, 2017;Savaş Tuna et al, 2017Souza et al, 2019). It has also been explained that geographical isolation (Pecinka et al, 2006;Wang et al, 2013), geographic distance (Savaş Tuna et al, 2019), deletion and duplication (Vlasova et al, 2016), and ecological selection (Wang et al, 2013) were effective in genome size variations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cytogenetic studies have been conducted to investigate the chromosomal structure of the common bean, which include chromosome analysis and cytogenetic maps [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Genome size information is an important issue in ploidy analysis, genome analysis, taxonomy, evolution, and breeding studies [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%